LIPID PROFILE AND KIDNEY FUNCTION IN PROLANIS PATIENT - Pratamawati, Tiar Masykuroh; Nauphar, Donny; Suhaeni, Eni (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2024)
Prolanis or Chronic Disease Management Program is a program from BPJS which aims to improve the quality of life for sufferers of chronic diseases such as diabetes mellitus and hypertension. The number of hypertension cases in Indonesia reaches 32.4% of the Indonesian population aged over 18 years. The prevalence of diabetes among those aged 20-79 years is 10.6%. Hypertension and diabetes mellitus can cause complications and even death. The aim of this study is to see the lipid profile and kidney function in kidney and hypertension patients. The method used in this research was descriptive with total sampling, blood tests were carried out to look at the parameters of total cholesterol, low-density lipoprotein (LDL), high-density lipoprotein (HDL), triglycerides, urea and creatinine in prolanis patients at the Mulya Medika clinic. The results were obtained from 24 hypertension patients and 10 diabetes mellitus patients with 18 people (53%) with high total cholesterol and 16 people (47%) with normal cholesterol, 23 people (68%) with high triglycerides and 11 people (32%) with normal cholesterol. %), HDL was low in 6 people (18%) and normal in 28 people (82%), creatinine in 34 people (100%) was normal and urea in 1 person (3%) was high and 33 people (97%) was normal. Conclusion 30 people (88%) prolanis had disorders in the lipid profile and 4 people (12%) were normal. Kidney function was abnormal in 1 person (3%) and 33 people (97%) were normal.